Apigenin as a therapeutic agent against cigarette smoke-induced cellular dysfunction: A comprehensive study on Beas-2B cells - Nabijan Mohammadtursun; Haibaier Huojiaaihemaiti; Muhammatjan Abduwaki; Alimujiang Paierhati; Jingcheng Dong (Traditional Medicine and Modern Medicine)
Cigarette smoke (CS) is a leading cause of respiratory diseases and cellular damage. Apigenin (Api), a natural flavonoid, exhibits antioxidant and anti-inflammatory properties, suggesting a potential protective role against cigarette smoke extract (CSE)-induced cellular damage. Aim: This study aimed to investigate the protective effects of Api on Beas-2B cells exposed to CSE. Methods: We optimized experimental conditions by treating Beas-2B cells with varying concentrations of Api (0 to 200[Formula: see text] [Formula: see text]mol/L) and CSE (1–30%) to determine the optimal concentrations and exposure times using the MTT assay for cell viability. Cells were then pretreated with 25, 50, and 100[Formula: see text] [Formula: see text]mol/L Api for 24[Formula: see text]h before a 4-h exposure to 5% CSE. The protective effects of Api were evaluated through multiple assays: cell viability (MTT), apoptosis and cell cycle analysis (flow cytometry), mitochondrial morphology (scanning electron microscopy), mitochondrial membrane potential and ATP content (TMRE), superoxide dismutase (SOD) activity (WST-8), and malondialdehyde (MDA) level (TBA). To elucidate the molecular mechanisms, we performed RNA sequencing to identify differentially expressed genes (DEGs) and conducted bioinformatics analysis. The PI3K/AKT and mitogen-activated protein kinase (MAPK) signaling pathways were confirmed using Western blot. Results: Api significantly increased Beas-2B cell survival within the tested concentration range ([Formula: see text]). CSE treatment for 4[Formula: see text]h significantly inhibited cell growth ([Formula: see text]), which was mitigated by Api pretreatment ([Formula: see text]), reducing apoptosis and modulating the cell cycle. Api also reduced MDA levels and enhanced SOD activity in CSE-treated cells ([Formula: see text]). RNA sequencing revealed 1761 DEGs in the Api-treated group compared to the CSE-only group, with 742 upregulated and 1019 downregulated genes, primarily associated with the MAPK and PI3K/AKT pathways. qPCR validation confirmed the top 10 upregulated and downregulated genes. Importantly, 50[Formula: see text] [Formula: see text]mol/L Api downregulated the protein expression of p-Akt, p-ERK, and p-MAPK in CSE-treated cells ([Formula: see text]). Conclusion: Our findings demonstrate that Api significantly reduces CSE-induced damage in Beas-2B cells, potentially through the inhibition of PI3K/AKT and MAPK signaling pathways and the regulation of multiple genes and mitochondrial function.